Comparison of the Effectiveness and Safety of d-Penicillamine and Zinc Salt Treatment for Symptomatic Wilson Disease: A Systematic Review and Meta‐Analysis - Tang, Shan; Bai, Li; Hou, Wei; Hu, Zhongjie; Chen, Xinyue; Zhao, Jing; Liang, Chen; Zhang, Wei; Duan, Zhongping; Zheng, Sujun (Frontiers in Pharmacology, 2022)
Background Pharmacological therapy is currently the main treatment method for patients with wilson disease (WD). We aimed to evaluate the efficacy and safety of the common treatment regimens in these patients. Methods We conducted a systemic review and meta-analysis by searching multiple databases for studies from inception to October 2021. Outcomes of interest were the improved rate and safety of D-penicillamine and zinc salts treatment in WD patients. Two independent reviewers performed the study selection and data extraction. Results Sixteen studies were included in this meta-analysis. The pooled improved rate for all included symptomatic WD patients was 78.0% (95% CI: 70.8% - 85.2%). In symptomatic hepatic WD patients, there is no difference in the treatment efficiency of D-penicillamine and zinc salts (RR: 0.98, 95% CI: 0.86- 1.12; p=0.765). In neurological WD patients, the pooled improved rate of those received D-penicillamine and zinc salts was 56.3% (95% CI: 37.5% - 75.1%) and 80.2% (95% CI: 67.2% - 93.2%), respectively. The incidence of adverse effects (RR: 2.42, 95% CI: 1.20- 4.88; p=0.014) and neurological deterioration (RR: 1.96, 95% CI: 1.31- 2.93; p=0.001) in all symptomatic WD patients treated with D-penicillamine was both higher than that of patients treated with zinc salts. Conclusions Our analysis suggests that symptomatic WD patients treated with D-penicillamine have higher incidence of adverse effects and neurological deterioration than that of zinc salts. The therapeutic effectiveness of these two regimens does not seem to be significantly different. And these results must be interpreted with caution. (PROSPERO registration: CRD 42021287126).